Analisis Strategi Guru dalam Menanamkan Karakter Disiplin Pada Siswa Kelas V di SDN Tlogorejo - Nisa, Ristiya Khoirun; Nugraheni, Luthfa; Ardianti, Sekar Dwi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research was motivated by the problems encountered at SDN Tlogorejo, namely the low level of discipline. Through these problems, teachers need to have strategies regarding instilling disciplined character in students. The aim of this research is to describe teacher strategies and obstacles that influence the growth of students' disciplined character. The research method used is qualitative research with a descriptive approach. Data collection techniques used were observation, interviews and documentation. The research results show that habituation and reinforcement are strategies carried out by teachers. The obstacles encountered include students' different abilities, students not being able to control their emotions, and an environment that is not conducive. The conclusion of this research is that the teacher's strategy for instilling discipline in students' character is by using habituation and reinforcement. There are obstacles that arise, including students' different affective abilities, controlling students' moods, and an environment that is not conducive.